Multifunctional polysaccharide composited microneedle for oral ulcers healing - Yiyu Zeng; Yijun Gao; Liming He; Wenhui Ge; Junhui Liu; Yi Yu; Xiaoyan Xie (Materials Today Bio, 2023)
Oral ulcers have periodicity and recurrence, and the etiology and causative mechanisms remain unclear; therefore, it is difficult to treat oral ulcers effectively. Current clinical treatment methods mainly include pain relief and administration of anti-inflammatories to prevent secondary infections and a prolonged recurrence cycle. However, these traditional treatment methods are administered independently and are susceptible to muscle movements and constant salivary secretion in the mouth, resulting in ineffective drug functioning. Therefore, development of a novel treatment to reduce wound infection and accelerate wound healing for oral ulcers is required for effective treatment. Herein, we report a multifunctional polysaccharide composite microneedle patch based on hyaluronic acid (HA) and hydroxypropyl trimethyl ammonium chloride chitosan (HACC) loaded with dexamethasone (DXMS) and basic fibroblast growth factor (bFGF) for oral ulcer healing. DXMS and bFGF encapsulated the HA tip portion of the microneedle patch, endowing the microneedle patches with anti-inflammatory and angiogenic properties. HACC was applied to the back of the microneedle patch, adding antibacterial properties. The experimental results indicated that the prepared dressings exhibited good antibacterial activity and effectively promoted cell migration growth and angiogenesis. More importantly, animal experiments have shown that multifunctional microneedle patches can effectively promote oral ulcer healing. Thus, these novel multifunctional polysaccharide composite microneedle patches have great potential for oral ulcers treatment.